THE TEACHER AS A CARRIER OF PLATFORM VALUE: RECOGNITION, STATUS, AND PARTICIPATION IN THE GOVERNANCE OF AN ONLINE EDUCATIONAL ENVIRONMENT - Filipov, Mariyan (E-Journal VFU, 2026)
This article examines the teacher and content creator in the online educational platform not as a peripheral executor, but as a carrier of content-related, pedagogical, and organizational value. The study is based on the understanding that the sustainability of the platform environment depends not only on its technological functionality or on learner activity, but also on its capacity to recognize and manage the contribution of participants who produce knowledge, maintain methodological quality, and participate in the continuous refinement of the environment. The central thesis is that sustainable teacher participation is a management-dependent variable: it is strengthened when the platform transforms contribution into recognizable professional validity, legitimate status, a visible pathway for role development, and a real opportunity for participation in governance. The theoretical framework combines the platform-based approach to management, knowledge management, the concept of intellectual capital, the literature on recognition and legitimacy, as well as the ideas of shared and distributed leadership. The article argues that the teacher remains a sustainable carrier of platform value when the system does not reduce their work to mere technical presence, but includes it within a transparent logic of recognition, accountability, and influence. The text contributes to the field of administration and management by offering a managerial reading of the teacher’s role in the online educational platform and by laying the groundwork for subsequent comparative studies on recognition, remuneration, and role development.
Keywords: online educational platform; platform governance; teacher role; recognition; status; role development; horizontal leadership; managerial legitimacy; accountability; sustainable participation